THEORETICAL STUDY OF THE ADSORPTION OF PROPIONIC ACID OVER Cu15</sub AND Pd15 CLUSTERS - F. O. Danilov; A. Yu. Skryabina; V. V. Zamalutin; R. S. Shamsiev (Тонкие химические технологии, 2013)
Now the world has a certain interest in methods for producing hydrocarbon fuels from fats. The most modern and advanced way of these reactions is the deoxygenation (decarbonylation / decarboxylation) acids. As catalysts for these reactions palladium nanoparticles are used. Now attempts are being made to replace it with a cheaper metal – copper or nickel. The mechanism of these reactions are currently poorly understood. Great help in resolving this issue may have a quantum-chemical methods. This paper describes the energy characteristics of the various structures that may be implemented in the adsorption molecule fatty acid on copper and palladium clusters.